2015
DOI: 10.11128/sne.25.tn.10305
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Methods in Heart Rate Variability: Can they Distinguish between Nonpathological and Pathological Subjects?

Abstract: Heart Rate Variability (HRV), i. e., the variation of time intervals between consecutive heart beats, is a marker of the health status, since it unveils changes in beat-to-beat variation of the heart, even before there is a remarkable change in heart rate itself. HRV reflects the balance between the sympathetic and the parasympathetic nervous system. The heart rate itself is nonstationary and the structure generating the signal involves nonlinear contributions. Thus, nonlinear methods to quantify the variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, this complex optimization tends to exhibit chaotic properties [34,35]. Because entropy is a measure of unpredictability and thus quantifies these chaotic properties, it can be concluded that a reduced HRV entropy reflects an impairment of the heart rate regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this complex optimization tends to exhibit chaotic properties [34,35]. Because entropy is a measure of unpredictability and thus quantifies these chaotic properties, it can be concluded that a reduced HRV entropy reflects an impairment of the heart rate regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Feature extraction and selection: In this stage, domain knowledge and data-driven approaches are utilized. In the domain knowledge, we selected the HRV measures among other vital signs mentioned in Table 1 due to many reasons: (a) the wellestablished connections in the literature between HRV features and pathological changes including inflammatory onsets [40,41], (b) the timely manner response of some HRV features such as the standard deviation of NN intervals (SDNN) and the root mean square of successive differences between normal heartbeats (RMSSD) [42]. Nonetheless, HRV is still nonspecific to certain inflammatory infections like the COVID-19.…”
mentioning
confidence: 99%